Senescence in Wound Repair: Emerging Strategies to Target Chronic Healing Wounds - Wilkinson, Holly N.; Hardman, Matthew J. (Frontiers in Cell and Developmental Biology, 2020)
Cellular senescence is a fundamental stress response that restrains tumour formation. Yet, senescence cells are also present in non-cancerous states, accumulating exponentially with chronological age and contributing to age- and diabetes-related cellular dysfunction. The identification of hypersecretory and phagocytic behaviours in cells that were once believed to be non-functional has led to a recent explosion of senescence research. Here we discuss the profound, and often opposing, roles identified for short-lived versus chronic tissue senescence. Transiently induced senescence is required for development, regeneration and acute wound repair, while chronic senescence is widely implicated in tissue pathology. We recently demonstrated that sustained senescence contributes to impaired diabetic healing via the CXCR2 receptor, which when blocked promotes repair. Further studies have highlighted the beneficial effects of targeting a range of senescence-linked processes to fight disease. Collectively, these findings hold promise for developing clinically-viable strategies to tackle senescence in chronic wounds and other cutaneous pathologies.